PERBEDAAN KEBIJAKAN FISKAL DALAM EKONOMI KONVENSIONAL DAN PERSPEKTIF ISLAM - Nelmy Fitria Utami; Desta Ayu Aristianti, Akhmad Kholil, Sendy Setia Ardifta, Suci Hayati (Jurnal Ekonomi dan Bisnis, 2025)
This article discusses a comparison between conventional fiscal policy and fiscal policy from an Islamic perspective, with a focus on their implementation during the time of the Prophet Muhammad (PBUH) and the Khulafa al-Rashidin. Conventional fiscal policy is based on macroeconomic principles that emphasize growth and stability through the management of taxation and government spending. In contrast, Islamic fiscal policy emphasizes social justice, wealth redistribution, and resource management in accordance with Sharia principles. This study employs a literature review method to analyze various sources related to both fiscal policy systems. The findings indicate that during the era of the Prophet and the Khulafa al- Rashidin, state financial management was conducted through the Bayt al-Mal with a transparent and accountable approach, successfully creating economic stability and societal welfare. The article also highlights the relevance of Islamic fiscal policy principles in the context of the modern economy and encourages further research on integrating ethical values into public budget management. Thus, this article provides valuable insights for policymakers aiming to develop a more inclusive and sustainable economic system.